Present and future etiological treatment of bacterial pneumonia 2. Antibiotic therapy of hospital-acquired pneumonia - А.Е. Abaturov; Т.А. Kryuchko (Zaslavsky O.Yu., 2017)
The choice of antibacterial drugs in the treatment of nosocomial pneumonia is a fairly complex clinical task that clearly depends on the etiology of the disease. According to the general guidelines of ATS/IDSA for antibacterial therapy, it is recommended for children with nosocomial pneumonia: to choose an antibiotic according to the sensitivity of the causative agent; to prefer the drugs with a limited range of antibacterial activity; to use a sufficient dose of antibiotic to provide an effective concentration at the site of infection. The first step in the algorithm for choosing an antibiotic may be taking into account the risk of multidrug-resistant pathogen as a causative agent of pneumonia.